Go loud or go home? How power distance belief influences the effect of brand prominence on luxury goods purchase intention - Aw, Eugene Cheng Xi; Hui, Stephanie Wen Chuah; Sabri, Mohamad Fazli; Kamal Basha, Norazlyn (Elsevier, 2021)
Based upon the signalling theory and self-congruity theory, this study theorizes and examines the effect of brand prominence on the purchase intention of luxury goods, with the mediating role of self-congruence and value-for-money perception. Furthermore, it explores the moderating effect of power distance belief. A single factor between-subject experiment study was conducted with a sample of 300 university students from Malaysia. Results suggest that the serial indirect effect of brand prominence on purchase intention through self-congruence and value-for-money perception is conditional upon the level of power distance belief. This study provides meaningful insight for marketing practitioners, as well as brand prominence literature by indicating how and when brand prominence works in evoking luxury goods purchase intention.